(untitled) (Pedagogical Cluster-Journal of Pedagogical Developments, 2024)
the article presents important corrective tasks in the process of teaching hearing perception and pronunciation, information on the formation and development of the skills of perception and reproduction of oral speech in children with hearing impairment.